Human and Organizational Factors in Occupational Accidents: An HFACS-Based Analysis at Company X in Japan - Fadel, Mohammad; Sabri Syahrir, Muhammad; Putri Hilintang, Rendhar; Bengang Lab, Stefani (Jurnal Locus Penelitian dan Pengabdian, 2026)
Occupational Safety and Health (K3) is a crucial aspect of the food manufacturing industry, which carries a relatively high risk of occupational accidents. This research aims to describe the factors that cause occupational accidents among workers at Company X in Japan using the Human Factors Analysis and Classification System (HFACS) approach. This study employs a quantitative method with an analytical descriptive design and involves the entire working population of 74 individuals through a total sampling technique. The variables analyzed include worker status, work shifts, compliance with the use of personal protective equipment (PPE), compliance with standard operating procedures (SOPs), and work areas. The results show that most workers (95.5%) had never experienced an occupational accident; however, the potential risk of accidents remains. The majority of workers are classified as compliant in the use of PPE (67.6%), but all respondents (100%) are recorded as non-compliant with SOPs. Most respondents were interns (58.1%) and worked in the packaging area (62.1%), with a relatively balanced distribution of work shifts between day and night shifts. Based on the HFACS analysis, the unsafe acts factor is indicated by non-compliance with PPE use; preconditions for unsafe acts are influenced by work shifts and work areas; unsafe supervision is reflected in the weak implementation of SOPs; while organizational influences are related to the predominance of interns and organizational policies. This study concludes that the potential for occupational accidents is influenced by both worker behavior and organizational systems.